Triboelectric speed bump as a self-powered automobile warning and velocity sensor. (June 2020) - Heo, Deokjae; Chung, Jihoon; Kim, Banseok; Yong, Hyungseok; Shin, Gunsub; Cho, Jung-Woo; Kim, Dongseob; Lee, Sangmin
Abstract: Intelligent transportation systems (ITSs) can be employed to solve problems such as traffic congestion and road accidents via the installation of self-powered sensors. Speed bumps are extensively used and have excellent potential for use as self-powered sensors in ITSs. Previous studies have considered harvesting energy from speed bumps based on electromagnetic, piezoelectric, and triboelectric effects, but the mechanical properties and suitability for mass production of commercial speed bumps were not considered. Herein, a practical speed bump triboelectric nanogenerator (SB-TENG) is proposed by considering the existing structures/materials and fabrication processes of commercial speed bumps. The SB-TENG comprises a commercial PVC speed bump as a body substrate and six copper electrodes. The overall structure is simple, electrode-inserted, and fully packaged. The SB-TENG can be used in both single-electrode and freestanding modes. The electrical performance of the SB-TENG is measured in terms of the peak and RMS outputs depending on the dynamic motion of the wheels as they pass over the speed bump. Through water and soil contamination tests, the SB-TENG is shown to generate electrical signals and recover its original output. Finally, we demonstrate that the SB-TENG can serve as a self-powered automobile warning sensor and velocity sensor in ITSs. Graphical abstract: Image 1 Highlights: Highly practical and suitable for mass-production speed bump TENG system using the commercial extrudable materials. First study to experimentally and theoretically analyze a speed bump TENG with respect to the rolling behavior of the tire. Self-powered sensor to detect and warn the public of approaching automobile and to measure the velocity of the automobile.